Practical dimensions of knowledge transfer in the diverse modern labour market – a research-based discussion - Pietruszka-Ortyl, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Nowadays knowledge has clearly gained the attribute of domination and has been widely recognized as the one from intangible resources, which has great importance for shaping competitive advantage. Knowledge, therefore, has become a new foundation of organisations’ well-being, and in the future the property will be the ability to gain control over knowledge. At present, we are pointing to a new dimension of social inequalities, the base of which is access to knowledge. Therefore, one of the ways of bridging these inequalities can be the conscious and controlled shaping of knowledge transfer between groups of knowledge agents, representing diverse, often overlapping, social and organizational categories. The study has a theoretical-empirical character. Its purpose is to synthesize a work on literature devoted to the transfer of knowledge and to indicate the dimensions of this process in view of the existing diversity in the labour market. The aim of the empirical part is to check in which groups of knowledge agents and by using which instruments, which sub-processes of knowledge transfer are implemented. The general research hypothesis is the assumption that the course of the knowledge transfer process depends on which groups of knowledge agents it concerns. It caused the emergence of detailed hypotheses and specific research questions. In order to find answers to these, the method of critical analysis and empirical research, based on a questionnaire based on in-depth interviews, was used. The results obtained from empirical research prove that sharing knowledge is the domain of professionalists and the dimension of the intergenerational exchange of knowledge. Acquiring knowledge is most often carried out at the level of specialists’ relations with other employees and between generations. Sharing knowledge is the domain of specialists and is usually and most often performed during their contacts with other employees. Dissemination of knowledge, in turn, is the chief subprocess of the hierarchical dimension of knowledge transfer.

Współcześnie wiedza bezspornie zyskała atrybut dominacji i została powszechnie uznana za ten z zasobów niematerialnych, który ma naczelne znaczenie dla kształtowania przewagi konkurencyjnej. Wiedza zatem stała się nową podstawą dobrobytu, a w przyszłości majątkiem będzie właśnie umiejętność sprawowania nad nią kontroli. Obecnie wskazuje się więc na nowy wymiar nierówności społecznych, jakim jest dostęp do wiedzy. Dlatego też jednym ze sposobów niwelowania tych nierówności może być świadome i kontrolowane kształtowanie transferu wiedzy między poszczególnymi grupami agentów wiedzy, reprezentującymi zróżnicowane, często nakładające się, kategorie społeczne i organizacyjne. Opracowanie ma teoretyczno-empiryczny charakter. Jego celem jest dokonanie syntezy dorobku literaturowego poświęconego transferowi wiedzy oraz wskazanie wymiarów tego procesu wobec istniejącego zróżnicowania na rynku pracy. Celem części empirycznej jest sprawdzenie, w jakich grupach agentów wiedzy i przy użyciu jakich instrumentów, które z subprocesów transferu wiedzy są realizowane. Ogólna hipoteza badawcza sprowadza się do sformułowania przypuszczenia, że przebieg procesu transferu wiedzy uzależniony jest od tego, których grup agentów wiedzy dotyczy. Spowodowała ona wyłonienie się hipotez szczegółowych oraz konkretnych pytań badawczych. Aby znaleźć na nie odpowiedzi wykorzystano metodę analizy krytycznej oraz badania empiryczne, zrealizowane w oparciu o kwestionariusz ankiety wsparty wywiadami pogłębionymi. Uzyskane wyniki badań empirycznych dowodzą, że dzielenie się wiedzą to domena profesjonalistów oraz wymiaru międzypokoleniowego wymiany wiedzy. Pozyskiwanie wiedzy jest najczęściej realizowane na poziomie relacji specjalistów z innymi pracownikami oraz międzypokoleniowym. Udostępnianie wiedzy jest domeną specjalistów i dokonuje się zwykle i najczęściej podczas ich kontaktów z innymi pracownikami. Rozpowszechnianie wiedzy z kolei, to naczelny subproces hierarchicznego wymiaru transferu wiedzy.
Keywords: knowledge transfer; diversification of the labour market; knowledge agents; transfer wiedzy; zróżnicowanie rynku pracy; agenci wiedzy